2016
DOI: 10.1186/s12974-016-0596-5
|View full text |Cite
|
Sign up to set email alerts
|

IL4 induces IL6-producing M2 macrophages associated to inhibition of neuroinflammation in vitro and in vivo

Abstract: BackgroundMyeloid cells, such as macrophages and microglia, play a crucial role in neuroinflammation and have been recently identified as a novel therapeutic target, especially for chronic forms. The general aim would be to change the phenotype of myeloid cells from pro- to anti-inflammatory, favoring their tissue-trophic and regenerative functions. Myeloid cells, however, display a number of functional phenotypes, not immediately identifiable as pro- or anti-inflammatory, and associated to ambiguous markers.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 41 publications
4
82
0
Order By: Relevance
“…In vivo experiments have shown that treatent of mice with LPS increases proinflammatory cytokines including IL-1β, but also IL-4R and further treatment with IL-4 induced the expression of Arg-1 as well as IL-1β, and this unique phenotype was able to promote neurite growth and spinal cord injury recovery (Fenn et al 2014). Furthermore, macrophages treated with IL-4 in vitro, were shown to produce IL-6 while co-expressing the M2 characteristic molecule CD206, and the co-expression of IL-6 did not affect immunosuppressive properties of the M2 phenotype macrophages (Casella et al 2016). Other studies aimed at characterizing specific molecules to delineate and identify microglia /macrophage phenotypes have also shown co-expression of the antiand pro-inflammatory phenotype markers (Chhor et al 2013, Gensel andZhang 2015).…”
Section: Microglia/macrophage Activation Phenotypementioning
confidence: 89%
See 2 more Smart Citations
“…In vivo experiments have shown that treatent of mice with LPS increases proinflammatory cytokines including IL-1β, but also IL-4R and further treatment with IL-4 induced the expression of Arg-1 as well as IL-1β, and this unique phenotype was able to promote neurite growth and spinal cord injury recovery (Fenn et al 2014). Furthermore, macrophages treated with IL-4 in vitro, were shown to produce IL-6 while co-expressing the M2 characteristic molecule CD206, and the co-expression of IL-6 did not affect immunosuppressive properties of the M2 phenotype macrophages (Casella et al 2016). Other studies aimed at characterizing specific molecules to delineate and identify microglia /macrophage phenotypes have also shown co-expression of the antiand pro-inflammatory phenotype markers (Chhor et al 2013, Gensel andZhang 2015).…”
Section: Microglia/macrophage Activation Phenotypementioning
confidence: 89%
“…Nowadays increasing evidence of mixed or overlapping microglia/macrophage phenotype can be found, and has been associated with the recovery after damage. IL-4 treatment of macrophages in vitro produced IL-6 and co-expressed CD206 (M2 marker) without affecting immunosuppressive properties of M2 phenotype macrophages (Casella et al 2016). Moreover, the expression of Arg-1 as well as IL-1β was associated with neurite growth promotion and spinal cord injury recovery (Fenn et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the roles of macrophage polarization in peripheral nerve injury and exercise have not been studied to date.Activation of the ligand-activated nuclear transcription factor peroxisome proliferator-activated receptor-γ (PPAR-γ) exerts beneficial effects through regulating the expression of genes relevant to inflammation, and to the monocyte/macrophages [12]. The pharmacological activation of PPAR-γ using high-affinity thiazolidinedione ligands can enhance IL-4-mediated priming of primary monocytes for differentiation towards an M2 macrophage phenotype in vitro (as measured by phenotypic marker studies involving the M2 marker the Mannose Receptor (MR) [13]. Recent study reports that low-intensity exercise can significantly increase PPAR-γ gene expression and activity in human leukocytes, cells that include circulating mono-cytes.…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 is required for the development of protective immunity to this pathogen, whereas IL-27 is required to limit infection-induced pathology [383] . IL-6 is known to mediate both pro-and antiinflammatory effects having two distinct ways to induce cell-signaling: either through the membrane bound receptor (antiinflammatory) or through trans-signaling (proinflammatory) [384] . This cytokine is the main stimulator of the production of most acute phase proteins [385,386] , and is important to the transition between acute and chronic inflammation [387] .…”
Section: T Gondii Infectionmentioning
confidence: 99%